Oral Reading Fluency: Teaching and Assessment Strategies - Aldhanhani, Zainab R. (2021)
Oral reading fluency skill is one of the keys to reading comprehension. Despite the significance of this skill, many reading curricula pay no attention to it [1]. Private schools in the United Arab Emirates (UAE) are giving great attention to reading fluency more than public schools. As a result, the current study adopted the exploratory qualitative design, in which three tools (documents analysis, classroom observations, and interviews) were employed respectively to investigate this issue in two private schools within the UAE. In particular, this study aimed: (1) to identify oral reading strategies used in private schools, (2) to identify the assessment strategies used to assess oral reading fluency, and (3) to identify if there is a match between the reading-aloud strategies and the assessment strategies used. Interestingly, the exploratory design helped to gain well-founded insights about the significance of teaching and assessing this skill. Moreover, the findings revealed English teachers’ practices in teaching and assessing students’ oral reading fluency. Teachers used plenty of reading-aloud strategies such as repeated reading, pair reading, individual reading-aloud, practice reading, choral reading, reading practice, and assisted reading to build and improve students’ reading fluency. It was also obvious that different assessment techniques were employed to assess students’ oral reading fluency such as the rubric, checklist, DIBLES: WCPM test, word efficiency test, and keeping records of students’ performance. Furthermore, it was clear that the aforementioned assessment tools were suitable with the reading-aloud instruction provided to the students. Notably, this research has contributed to the limited body of knowledge within the UAE about the significance of integrating reading-aloud strategies in any reading programs to develop students’ fluency and comprehension. The study bridged the gap in the literature through exploring more than one strategy and more than one assessment tool used to boost students’ oral reading fluency. According to the previous findings, fostering oral reading fluency and creating a better reader, who reads fluently should be taken into account. Therefore, oral reading fluency should not be neglected. Policymakers and curriculum designers have to think of incorporating teaching and assessing oral reading fluency into reading programs and curriculum.